Integrative Nadi Sodhana and Self-Hypnosis Mind Body Intervention to Improve Self Esteem and Mindfulness Among Adolescents - Luh Putu Widiastini; Putu Ayu Dina Saraswati; Ni Luh Putu Dian Yunita Sari (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2025)
Introduction: Adolescents often face psychological challenges such as low mindfulness and self-esteem, which can increase their vulnerability to emotional distress. Nadi Sodhana Pranayama and Self-Hypnosis have been identified as mind–body techniques that may improve emotional regulation and self-perception, yet their combined effect in adolescent populations is understudied. Objective: This study aimed to examine the effectiveness of combined Nadi Sodhana Pranayama and Self-Hypnosis interventions in enhancing mindfulness and self-esteem among female adolescents. Methods: We used a quasi-experimental nonequivalent control group structure. Purposive sampling identified forty-seven seventh-grade female students from the SMP Negeri Abiansemal; these students were split into treatment (n = 20) and control (n = 20) groups. Twice daily, for three straight days, the intervention consisted in ten minutes of Nadi Sodhana mixed with fifteen minutes of guided self-hypnosis. The five-facet mindfulness questionnaire (FFMQ) and Rosenberg Self-Esteem Scale (RSES) were used in pretest and post-test evaluations. T tests both paired and independent helped to examine the data. The STIKES Bina Usada Bali Ethics Committee (number 081/EA/KEPK-BUB-2025) gave ethical approval. Results: The treatment group showed significant improvements in mindfulness (p = 0.004) and self-esteem (p = 0.015) compared with the control group. No significant changes were observed in the control group. The between-group effect size was moderate for mindfulness (Cohen’s d = 0.40) and large for self-esteem (Cohen’s d = 0.96), indicating the practical impact of the intervention. Conclusion: The combination of Nadi Sodhana Pranayama and Self-Hypnosis is effective in enhancing mindfulness and self-esteem in adolescents. This approach is feasible for school-based mental health programmes.